COMPARISON OF TWO AEROSOL-FREE CARIES REMOVAL METHODS - A SPLIT MOUTH RANDOMIZED CLINICAL TRIAL - Canan Duman; Elif Kalaoğlu; Belen Şirinoğlu Çapan; Edibe Egil (Cumhuriyet University, 2021)
Objectives: The management of deep caries lesions in immature permanent molars might be challenging in clinical practice. Minimally invasive caries removal methods can maintain apexogenesis by preventing extensive tissue loss. Here we compare the chemo-mechanical caries removal (CMCR) gel and the polymer bur in terms of time spent on caries removal, patient acceptability, and clinical success. Materials and Methods: The teeth of 30 children were randomly divided into two groups. The duration of each method, the level of cooperation during each method, and the child's choice of caries removal method were recorded. Patients were followed at 6-month intervals for at least 2 years. Results: The difference between the patients' preferences was not statistically significant, while the average caries removal time of the polymer bur method was significantly shorter (p < 0.05). The rates of apical closure without pathology in CMCR and polymer bur groups were 63.2% and 73.7%, respectively, whereas 10% of each group underwent further treatments due to the clinical and/or radiographic pathology. Conclusions: These methods were thought to serve as an interim treatment in managing immature permanent teeth with deep caries. Furthermore, these methods, which do not involve water cooling, can also minimize the risk of contamination and cross-infection.